2023 MPD Student Poster Contest – Winning Abstracts - Mining, Metallurgy & Exploration (2023) - Chee Theng (Society for Mining, Metallurgy & Exploration, 2023)
The Mineral & Metallurgical Processing Division (MPD) of the Society for Mining, Metallurgy & Exploration held the 13th MPD Student Poster Contest on March 1, 2023, during the MINEXCHANGE 2023 SME Annual Conference & Expo. The event showcased the work of 24 graduate and undergraduate students from U.S. and international institutions. The contest began in January when the students submitted one‐page abstracts for judging. In February, they prepared and presented posters that explained their research, and each student had five minutes to showcase their research to a panel of judges during the conference. In recognition of their efforts, the MPD provides monetary rewards to all participants. For graduate students, first place receives $1,000, second place $500, and third through seventh places $200 each, and for undergraduate students, first place receives $1,000 and second place $500. The main authors of nonplacing entries receive $125 each. Participation in the contest also includes a free ticket to the MPD Luncheon, where the winners are announced.